Hearing Impairment and Its Correlates Among Newborns at Tertiary Care Hospital of Surat - Patel, Rajnikant; Goyani, Rajesh; Patel, Dhwani (National Journal of Community Medicine, 2015)
Introduction: Hearing impairment has a devastating, detrimental and an invariably adverse impact on the development of new-borns and the psychological well-being of their families. Objective: To study the incidence and prevalence of hearing impairment and its correlates in the high risk neonates in Neonatal Intensive Care Unit (NICU). Methodology: This cross sectional study was conducted at NICU of Surat Municipal Institute of Medical Education and Research (SMIMER) between 1st August 2012 to 30th October 2013 after taking written consent of parents and approval of institutional ethical com- mittee. Results: Among high risk new born 36 (27.6%) new born had hearing impairment. Multiple risk factor increases the risk for hearing im- pairment in newborns as compared to single risk factor. Newborns with birth weight ≤ 1.5 kg were 2.341 times (CI: 1.15- 4.763) more prone to develop hearing impairment. Conclusion: The incidence of hearing impairment was 13% in new- borns admitted in NICU in our hospital. Factors like early gestational age, low birth weight, birth asphyxia, hyperbillirubinemia, ventilator support and TORCH infection were significantly found to be asso- ciated with hearing impairment.